Features of forensic psychological examination in the investigation of criminal cases of crimes committed by minors - Dzhansarayeva, R.Y.; Duzbayeva, S.B.; Borankulova, K.B. (KU Publ., 2021)
The article deals with the issues of appointment and carrying out of forensic psychological examination in relation to minors. Forensic psychological examination in criminal cases involving minors is usually appointed to establish the ability of an accused, suspect, defendant minor with a mental retardation not related to a mental disorder to fully realize the actual nature and social danger of their actions and to direct them; to determine the ability of juvenile witnesses and victims to correctly perceive the circumstances relevant to the case and give correct testimony about them; to determine the ability of juvenile victims in cases of sexual assault to understand the nature and significance of actions committed against them and to resist. In connection with the age characteristics of a minor, in particular during the period of deep experiences occurring against the background of personal conflicts and physiological changes, it is necessary to take into account the individual characteristics of a minor, the peculiarities of upbringing, etc. The authors concluded that forensic psychological examination allows with respect to the research of criminal cases from each objective speck of view to take into account the rank and ableness of a teenager to make out the design of his actions and come this from a deeper scientific sharp end of contemplate than other types of examinations.
Кəмелетке толмағандар жасаған қылмыстар туралы қылмыстық істерді тергеу кезіндегі сот-психологиялық сараптаманың ерекшеліктері
Особенности судебно-психологической экспертизы при расследовании уголовных дел о преступлениях, совершенных несовершеннолетними
Keywords: examination; forensic psychological examination; production of forensic psychological examination; forensic psychological examination of minors; age